The Challenge of Ambient Air–Processed Organometallic Halide Perovskite: Technology Transfer From Spin Coating to Meniscus Blade Coating of Perovskite Thin Films - Fong, Patrick Wai-Keung; Li, Gang (Frontiers in Materials, 2021)
The development of perovskite solar cells (PSCs) has been extensively studied in the past decade and the power conversion efficiency (PCE) has reached a record of 25.2%. Despite impressively high PCE, the fabrication process mainly relied on a well-controlled environment, inert gas-filled glovebox, and devices of small areas were demonstrated. This impedes the technology transfer from laboratory scale spin coating to manufacture ambient air scalable processes. Furthermore, the nucleation and crystal growth processes of the perovskite thin films are different when the films are prepared in different environmental conditions. In this review, we summarize the recent advances of ambient air-processed organometallic halide perovskite thin films. Focuses are made on the impact of ambient air conditions, typically adventitious moisture, on the crystallization of perovskites thin films. The challenges and strategies in the technology transfer from glovebox or ambient air spin coating to scalable meniscus blade coating are also discussed to shed the lights on the manufacturing of ambient air-processed PSCs.